A randomized Phase I pharmacokinetic trial comparing the potential biosimilar trastuzumab (SIBP-01) with the reference product (Herceptin®) in healthy Chinese male volunteers. (2nd October 2020) - Zhou, Huan; Cao, Shugang; Zhu, Xingyu; Xie, Jing; Fan, Ling; Ge, Qin; Wang, Ying; Zhu, Juan; Liu, Yuanyuan; Shao, ZhongHuan; Shan, Rongfang; Liu, Bingyan; et al.
ABSTRACT: Objectives: This study aimed to evaluate the bioequivalence, safety, tolerability and immunogenicity of the biosimilar trastuzumab (SIBP-01) compared to Herceptin®. Methods: In this Phase I randomized double-blind parallel-group trial, 100 healthy male volunteers were randomized in a1:1 ratio to receive a single 6 mgkg–1 intravenous dose of SIBP-01 or Herceptin®. Serum concentrationswere analyzed using a validated ELISA. Results: The two groups had similar baseline characteristics. The geometric mean ratios (90% CI) of Cmax, AUC0-t and AUCinf between the trial group and the reference group were 93.55%-104.27%, 91.98%-102.35% and 91.88%-102.34%, respectively; the geometric mean ratios (90% CI) of AUC0-t and AUCinf in the sensitivity analysis were 92.29%-102.63% and 91.81%-102.16%, respectively. These values were within the prespecified equivalence margins, establishing the bioequivalence of SIBP-1 and Herceptin®. AEs were similar across all subjects in the SIBP-01 and Herceptin® arms, with treatment-related AEs reported by 72.00% and 80.00%, respectively. In each group, there was one AE that caused a subject to discontinue the study. Expert opinion: Trastuzumab (Herceptin®) is significantly more effective than chemotherapy in reducing exacerbations and tumor cell growth, and its adverse events are far lower than chemotherapy. Herceptin®is very expensive for most patients in China. The protein molecular primary structure of the biosimilar trastuzumab (SIBP-01) is consistent with Herceptin®, with highly similar high level structure, biologocal activity and purity.But there are few studies comparing the bioequivalence of SIBP-01 and Herceptin® in healthy subjects and cancer patients 2 . Conclusions: This study showed the PK similarity of SIBP-01 to Herceptin®. SIBP-01 was safe and well tolerated in healthy male volunteers, with no significant differences from the reference drug in safety or immunogenicity 4 .